Does muscle fatigue change motor synergies at different levels of neuromotor control? - Pawłowski, Michał; Furmanek, Mariusz P.; Juras, Grzegorz (Frontiers in Human Neuroscience, 2025)
We investigated the effects of static and dynamic fatigue on motor synergies, focusing on their hierarchical control. Specifically, we examined whether changes in fatigue influence the central nervous system’s ability to preserve movement stability. In addition to exploring the direct impact of fatigue on motor synergies, we also analyzed its effects at two distinct levels of hierarchical control, aiming to elucidate the mechanisms by which fatigue alters motor coordination and stability. Thirteen healthy, young and right-handed male participants took part in the study. Participants performed a bilateral accurate force production task under static and dynamic fatigue conditions at 30% of maximal voluntary contraction level with elbow flexors. Muscle activity level were collected from five muscles of each limb: biceps brachii, brachialis, brachioradialis, flexor carpi radialis, and flexor carpi ulnaris. The results revealed distinct effects of fatigue on isometric force production in the elbow joint tasks. On the higher level of hierarchy control of synergies, there were non-significant effects of different types of fatigue on movement performance, however, on the lower level we observed a strong effect of fatigue on forming motor synergies. There was no significant difference between the type of applied fatigue protocol on force and muscle activity data, nevertheless, the contribution of involved muscles to the task has changed. Our findings indicate that the central nervous system employs specific strategies to counteract fatigue and preserve movement stability during performance. However, the precise mechanisms by which variability at lower levels of hierarchical control influence higher levels remain unclear, highlighting a critical gap in our understanding of motor coordination under fatigue. Future studies should explore how these interactions across hierarchical levels contribute to movement stability under different fatigue conditions.